Ghosts in the mind's machine - "Kosslyn, Stephen Michael" (New York, 1983)
The book is narrative of how the author and a group of researcher investigation of the process of mental imaging, explains the strategies of the investigation and the role of the computer in the research, and elucidates complex functions of human memory and thinking.
Keywords: Imagery -Psychology